Effect of Volume Fraction and Matrix of Forged Fibreglass Composite on Wear Rate for Brake Pad Application - Wihardias, Angga Faisal; Fakhruddin, Muhammad; Muzaki, Mochamad; Pramita Sari, Nurlia (Journal of Engineering and Applied Technology, 2025)
Brake pads are one of the components of motorised vehicles that play an important role in slowing down or stopping the vehicle. This study aims to determine the effect of using variations in volume fraction and type of resin/matrix used on the wear rate that occurs, and the temperature generated during braking by utilising glass fibre as reinforcement. The research method uses experiments where the manufacture of brake pads composites was carried out by mixing all the ingredients then poured in a mold with a curing time of 1 day and the next process was testing using a disc brake system braking simulator and a thermal imaging camera with a variation in the percentage of glass fiber 45%, 55%, 65%, 75% and the type of resin used was epoxy resin and polyester. The results of this study indicate the effect of the type of resin/matrix used on the value of the wear rate that occurs. The test results show that the smallest wear rate is owned by specimen code D of 0.000000081 g/mm2.second with epoxy as the type of resin used. Then the largest wear rate is owned by specimen A1 of 0.000000154 g/mm2.second with polyester as the type of resin. It can be concluded that the higher the density of the polymer material, the lower the wear rate. It is expected that the composite brake pads have improved physical and mechanical properties that are better than the original brake pads.